Educación diabetológica, adherencia terapéutica y proveedores de salud - Casanova Moreno, María de la Caridad; Bayarre Vea, Héctor Demetrio; Navarro Despaigne, Daysi Antonia; Sanabria Ramos, Giselda; Trasancos Delgado, Maricela (Revista Cubana de Salud Pública, 2015)
/